Respon Pertumbuhan Indigofera (Indigofera zollingeriana) yang Diberikan Pupuk Kotoran Kelinci dan Biochar - Gresy Eva Tresia; A. Saenab (Universitas Sulawesi Barat, 2020)
Application of organic manures for improvement soil fertility is expected to increase productivity of Indigofera zollingeriana in marginal land agro-ecosystems.The aim of this study was to evaluate the growth response of Indigofera zollingeriana on application of rabbit and biochar fertilizers. This study used a completely randomized design with 3 treatments and 10 replications. The treatments consisted of T0 (chicken manure biofertilizer as control), T1 (biochar), and T2 (biochar + rabbit manure biofertilizer). The variables observed were stem height (cm), number of stalks, and number of leaves. Application of rabbit manure biofertilizer and biochar (T2) gave the highest plant height, number of stalks and leaves Indigofera of 45.68±4.18 cm, 35.80±1.03 stalk, and 128.5±11.65 leaves, respectively. Also, application T2 enhanced growth vegetative Indigofera started at 7 weeks of age (35th days after planting). It could be concluded that the combination of biochar and rabbit manure biofertilizer gives the optimal result in the growth of Indigofera.